Study Protocol - an exploratory trial on health promoting schools at Dutch secondary schools - Vincent Busch; Rob Johannes De Leeuw; Augustinus Jacobus Schrijvers (International Journal of Integrated Care, 2012)
Background: Recent studies show adolescent health-related behaviours to co-occur synergistically. This paper describes the study design for an exploratory trial on the effects of a comprehensive, whole-school health promoting school intervention. This intervention tackles seven different behavioural domains simultaneously via a combination of education, creating a healthy environment and introducing healthy behavioural policies. Additionally, extensive partnerships are formed between schools, parents, neighbourhoods and youth health authorities to coordinate health promotion efforts. Study design and data collection methods: The intervention will be implemented at two secondary schools. Results will be compared with two control schools (n≈1500). The intervention's effectiveness in changing student behaviours as well as physical and psychosocial health status along with qualitative lessons learned on the integration of youth health care services and school health education practices are the main aimed outcomes of this study. Data are collected via a mixed methods design combining an annual youth health (behaviour) monitor with a qualitative process evaluation via interviews with key stakeholders. Data analysis: A multilevel analysis is performed combined with a systematic analysis of qualitative interview data. Conclusions: This study will produce an evaluation of a comprehensive health promoting school intervention that combines an integrated approach of schools, neighbourhoods, families and youth health services to improve adolescent health.